Transferability of microsatellite markers located in candidate genes for wood properties between Eucalyptus species - Acuña, Cintia Vanesa (2014)
AIM OF STUDY: To analyze the feasibility of extrapolating conclusions on wood quality genetic control between different Eucalyptus species, particularly from species with better genomic information, to those less characterized. For this purpose, the first step is to analyze the conservation and cross-transferability of microsatellites markers (SSRs) located in candidate genes. AREA OF STUDY: Eucalyptus species implanted in Argentina coming from different Australian origins. MATERIALS AND METHODS: Twelve validated and polymorphic SSRs in candidate genes (SSR-CGs) for wood quality in E. globulus were selected for cross species amplification in six species: E. grandis, E. saligna, E. dunnii, E. viminalis, E. camaldulensis and E. tereticornis. MAIN RESULTS: High cross-species transferability (92% to 100%) was found for the 12 polymorphic SSRs detected in E. globulus. These markers revealed allelic diversity in nine important candidate genes: cinnamoyl CoA reductase (CCR), cellulose synthase 3 (CesA3), the transcription factor LIM1, homocysteine S-methyltransferase (HMT), shikimate kinase (SK), xyloglucan endotransglycosylase 2 (XTH2), glutathione S-transferase (GST), glutamate decarboxylase (GAD) and peroxidase (PER). RESEARCH HIGHLIGHTS: The markers described are potentially suitable for comparative QTL mapping, molecular marker assisted breeding (MAB) and for population genetic studies across different species within the subgenus Symphyomyrtus.